Genome-wide in silico identification, characterization and transcriptional analysis of the family of growth-regulating factors in common bean (Phaseolus vulgaris l.) subjected to polyethylene glycol-induced drought stress - Büyük, İlker; Aras, Sümer (Archives of Biological Sciences, 2017)
According to most recent findings, growth regulating factors (GRFs) are plant-specific transcription factors (TFs) that play important roles in many processes, including abiotic and biotic stress response mechanisms. Completion of the common bean (Phaseolus vulgaris) genome project has provided researchers with the opportunity to identify all GRF genes in this species. With this aim, a genome-wide in silico study was performed and 10 GRF proteins (called PhvGRFs) were identified in the common bean genome. Conserved and mandatory motifs (QLQ and WRC) were confirmed in all identified PhvGRFs and two segmental duplication events were determined. Most of the PhvGRFs were found to be more similar to Arabidopsis thaliana GRFs than to Zea mays GRFs in a phylogenetic tree. According to the expression analysis of 10 PhvGRFs, inversely related expression patterns were observed in the roots of Yakutiye and Zulbiye cultivars based on their capacity to adopt to drought stress. After drought treatment of the Zulbiye cultivar, a drought-sensitive common bean cultivar, PhvGRF1, PhvGRF2, PhvGRF3, PhvGRF5, PhvGRF6, PhvGRF9 and PhvGRF10 genes were upregulated 2- to 4-fold in root tissues, as compared to the untreated control. The trend of PhvGRF1, PhvGRF2, PhvGRF3, PhvGRF5, PhvGRF6, PhvGRF7, PhvGRF9 and PhvGRF10 genes showed a consistent decline of 2- to 6-fold in root tissues of the drought-tolerant Yakutiye cultivar subjected to 24 h of drought stress. We demonstrated that the expression patterns of the identified PhvGRFs correlated with the drought-stress response in a cultivar-specific manner in the common bean. We suggest that members of the GRF family can also be used for genetic engineering applications in the common bean. DOI:10.2298/ABS160204033B Received: February 4, 2016; Revised: March 21, 2016; Accepted: March 25, 2016; Published online: April 4, 2016 How to cite this article: Büyük İ, Aras S. Genome-wide in silico identification, characterization and transcriptional analysis of the family of growth-regulating factors in common bean (Phaseolus vulgaris l.) subjected to polyethylene glycolinduced drought stress. Arch Biol Sci. 2017;69(1):5-14.